(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research was carried out in the coastal region of Syria in 2021 and targeted both rural and urban areas with the aim of measuring the level of food expenditure, its characteristics, and the flexibility of income expenditures for families residing in it. Especially under the conditions of the stifling economic crisis that Syria suffers from which is reflected in the food security situation. The research relied on primary data collected from field surveys targeted a random sample of consumer families amounted to 384 families, distributed throughout 45% of rural areas. The research results shows that the flexibility of food consumption of each sample is less than one in general, where doubling the income will lead to direct 57% of it to the food group, and the remaining 43%, to the rest of the non-food commodity groups. It is noted that the amount allocated to food expenditure for rural families is 38% higher compared to urban families, which indicates a low nutritional status of the sample level in general, and for rural families in particular.